(untitled) (American Journal of Islam and Society, 2011)
Fred Donner’s Muhammad and the Believer’s at the Origins of Islam is the most recent in a long line of books that have attempted to recast the narrative of the early history of Islam in ways that seek to challenge both traditional Islamic readings of the sources and previous academic scholarship. Donner explicitly states that his book has two goals. The first is to challenge the notion that he sees as permeating Western scholarship on Islam: that the Prophet Muhammad (ṢAAS) and his followers were mainly motivated by factors other than religion ‒ that is to say, that Islam was more of a political movement than a religious one. On this point, Donner argues persuasively that the primary motivation guiding the Prophet and his movement was religious and that his message was a clarion call to monotheism and piety that built upon Christianity and Judaism. More controversially, Donner argues that the Prophet Muhammad was less the founder of a new religious community than “an inspired visionary” who “inaugurated a pietistic religious movement that we can best call, followings its adherents own usage, the Believers movement (86‒87).” This movement was not in its origins a new religion but instead an ecumenical community, which included not only Arabs newly converted to monotheism but also Christians and Jews. Donner’s second task is to counter the notion that that the Umayyads were “cynical manipulators of the outward trappings of the religious movement begun by Muhammad (xii).” Instead, Donner seeks to rehabilitates the Umayyads “as rulers who sought practical ways to realize the most important goals of the movement and perhaps more than anyone else helped the Believers attain a clear sense of their own distinct identity and of their legitimacy as a religious community (xii).” ...